International handbook of migration and population distribution - White, Michael J. (New York : Springer, 2016)
This Handbook offers a comprehensive collection of essays that cover essential features of geographical mobility, from internal migration, to international migration, to urbanization, to the adaptation of migrants in their destinations. Part I of the collection introduces the range of theoretical perspectives offered by several social science disciplines, while also examining the crucial relationship between internal and international migration. Part II takes up methods, ranging from how migration data are best collected to contemporary techniques for analyzing such data. Part III of the handbook contains summaries of present trends across all world regions. Part IV rounds out the volume with several contributions assessing pressing issues in contemporary policy areas. The volume's editor Michael J. White has spent a career studying the pattern and process of internal and international migration, urbanization, and population distribution in a wide variety of settings, from developing societies to advanced economies. In this Handbook he brings together contributors from all parts of the world, gathering in this one volume both geographical and substantive expertise of the first rank. The Handbook will be a key reference source for established scholars, as well as an invaluable high-level introduction to the most relevant topics in the field for emerging scholars.
Includes bibliographical references and index.
Description based on publisher-supplied MARC data.
Keywords: Emigration and immigration; Demography